2017
DOI: 10.1136/bmj.j3544
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial policy interventions in food animal production in South East Asia

Abstract: Flavie Goutard and colleagues call for concerted multisectoral measures through stronger policies to combat antimicrobial resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 6 publications
2
66
0
2
Order By: Relevance
“…Furthermore, poor infection control practices in farms lead to the selection and spread of resistant strains. 31 Antibiotic use in livestock is expected to rise because of increased production in response to a growing demand for food from animal sources. 32 International food safety and quality standards have reduced antibiotic use in animal products intended for export; however, the same is not true for livestock products for domestic consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, poor infection control practices in farms lead to the selection and spread of resistant strains. 31 Antibiotic use in livestock is expected to rise because of increased production in response to a growing demand for food from animal sources. 32 International food safety and quality standards have reduced antibiotic use in animal products intended for export; however, the same is not true for livestock products for domestic consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Russia is also backing FAO-led efforts to promote food safety and prevent AMR in Central Asia and Eastern Europe (FAO, 2017). In reaction to new WHO initiatives, Bangladesh, Bhutan, Indonesia, Myanmar, Nepal, Sri Lanka, and Thailand have similarly announced agricultural antibiotic restrictions and national action plans (Goutard, 2017).…”
Section: From European To Global Reformmentioning
confidence: 99%
“…A 2017 review of the WHO's South East Asia Region (SEAR) found that many SEAR states did not enforce regulations or monitor antibiotic use in agri-and aquaculture (Goutard, 2017). In Russia, the past 18 years have seen a sharp rise in agricultural antibiotic use and imports.…”
Section: Through the Looking Glassmentioning
confidence: 99%
“…Most of the countries in this region have some policy structure (either policy-inplace or policy-in-making) regarding the use of antimicrobials in food animals and fish. For example, the use of antimicrobials is banned as a food additive in some of these countries for rearing food animals, but implementation remains a problem due to the weak regulatory regime [5]. This is also true for policies to prevent contamination of the environment with antimicrobial residues from human and animal use [6].…”
Section: Introductionmentioning
confidence: 99%